2023
DOI: 10.1001/jamaoncol.2022.4933
|View full text |Cite
|
Sign up to set email alerts
|

Association of Machine Learning–Based Assessment of Tumor-Infiltrating Lymphocytes on Standard Histologic Images With Outcomes of Immunotherapy in Patients With NSCLC

Abstract: ImportanceCurrently, predictive biomarkers for response to immune checkpoint inhibitor (ICI) therapy in lung cancer are limited. Identifying such biomarkers would be useful to refine patient selection and guide precision therapy.ObjectiveTo develop a machine-learning (ML)-based tumor-infiltrating lymphocytes (TILs) scoring approach, and to evaluate TIL association with clinical outcomes in patients with advanced non–small cell lung cancer (NSCLC).Design, Setting, and ParticipantsThis multicenter retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 37 publications
(51 reference statements)
1
29
0
Order By: Relevance
“…The GSVA results revealed that CDK1 also plays a role in immune regulation, especially in T cells. Tumor-infiltrating lymphocytes have been reported as a predictor of disease progression and to be related to the efficacy of immunotherapy in non-small cell lung cancer (NSCLC) patients ( 17 , 18 ). Here, we next performed a comprehensive analysis to investigate the relationship between CDK1 expression and tumor immune microenvironment factors, including lymphocytes, checkpoints, MHC molecules, chemokines and receptors.…”
Section: Resultsmentioning
confidence: 99%
“…The GSVA results revealed that CDK1 also plays a role in immune regulation, especially in T cells. Tumor-infiltrating lymphocytes have been reported as a predictor of disease progression and to be related to the efficacy of immunotherapy in non-small cell lung cancer (NSCLC) patients ( 17 , 18 ). Here, we next performed a comprehensive analysis to investigate the relationship between CDK1 expression and tumor immune microenvironment factors, including lymphocytes, checkpoints, MHC molecules, chemokines and receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the analytical validity may be implemented through web-based platforms aiming at enhancing the interaction among pathologist and increasing the concordance of morphological assessment, as demonstrated in TONIC trial (NCT02499367), in which concordance values between four pathologists were >90%; and through the development of operator-independent approaches (e.g., machine-learningbased) [71][72][73].…”
Section: Future Challenges and Conclusionmentioning
confidence: 99%
“…For example, a meta-analysis of 22 studies, including 1569 patients with early BC who received TIL dynamic assessment during NACT, demonstrated that an increase in TILs in TNBC was associated with better DFS in univariate analysis (HR: 0.59; 95% CI: 0.37-0.95; p = 0.03) [74]. Furthermore, TILs levels were assessed in patients with TNBC who had Furthermore, the analytical validity may be implemented through web-based platforms aiming at enhancing the interaction among pathologist and increasing the concordance of morphological assessment, as demonstrated in TONIC trial (NCT02499367), in which concordance values between four pathologists were >90%; and through the development of operator-independent approaches (e.g., machine-learning-based) [71][72][73].…”
Section: Future Challenges and Conclusionmentioning
confidence: 99%
“…A negotiating strategy that leaders use is to ask, “What would it take?” In light of the weak predictive biomarkers used for immune checkpoint inhibitor (ICI) therapy, it may be time to ask the pathologist “What would it take to provide us with a quantitative tumor infiltrating lymphocyte (TIL) score for each patient with non–small-cell lung cancer?” In this issue of JAMA Oncology , Rakaee et al describe a new biomarker associated with response to ICI based on an objective, open-source, machine learning (ML) method using QuPath software to count TILs in lung cancer. They note that TIL has potential to improve selection of responders to ICI and that ML-TIL is easily obtained, accurate, and reproducible.…”
mentioning
confidence: 99%
“…Clearly 1 or 2 were not enough, or we (pathology laboratories) would all be digital. Perhaps the sorts of assays like that described by Rakaee and colleagues, combined with similar either open-source or proprietary assays, will eventually provide sufficient improvement in patient care or reimbursement to trigger broad adoption.…”
mentioning
confidence: 99%